Faktor – Faktor Yang Mempengaruhi Impor Beras Di Indonesia Tahun 2015 – 2021 - Istifaria Inka Handini; Muhammad As’ad (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The objective of this study is to find out the influence of Rice Production, Price of Oversea Rice and Exchange Rate collectively against importation of rice and the influence of Quantity of Rice Production, Price of Oversea Rice and Currency Exchange Rate partially to the importation of Indonesia Rice year 2015 – 2021. This study used secondary data with quantitative approach. In this study applied simple linear regression and multiple linear regression analysis with use of SPSS 25. Result of Simultaneous Test (F test), identified that Rice Production, Oversea Rice Price and currency Exchange Rate simultaneously influencing Importation of Indonesia Rice.  Result of T Test identified that Rice Production from such output resulted Adjusted R Square in the amount of 0.559, Oversea Rice Price from such output resulted Adjusted R Square in the amount of 0.088 and Currency Exchange Rate of such output resulted Adjusted R Square in the amount of 0.083 influencing not significant negative against Importation of Indonesia Rice.